Refleksi Sistem Pangngaderreng dalam Sosial Budaya Bugis-Makassar: Analisis Putusan Pengadilan Agama - Fikri Fikri (Al-'Adl, 2016)
Islamic law as the law of life that is living law in a society refleksitas social behavior of individuals. Islamic law also believed to be the soul or spirit of the community in managing an individual's life when the interaction between one and the other as a social being. Islamic law in the life of society is no longer seen as the rules but also the behavior. Through behavioral, cultural interpretation by humans discovered the laws that apply to him. In turn Islamic law are considered potent provide a solution when there is a social problems that arise in the life of society. Pangngaderreng or pangngadakkang systems that organize and regulate the legal matters of inheritance and marriage laws in force in the social and cultural Bugis-Makassar no small raises diversity issues in family law. Moreover, the existence of the Religious Court as a state institution has a role to complete each particular case of the Islamic community in the form of a ruling. The court ruling Religion, has permanent legal force that can be executed with forceful measures, so that the public must submit and obey the decision of the judge in court.